Therapy of pancreatic cancer with alternating electric fields: limitations of the method - Pfeifer, Tobias; Bai, Liping; Gladkich, Jury; Gross, Wolfgang; Liu, Li; Herr, Ingrid; Schäfer, Michael (Bioelectrochemistry, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumor with a poor prognosis. More effective treatment options are urgently needed. The use of physical and weak alternating electric fields (TTFields) can inhibit cell division of PDAC carcinoma and is currently being investigated in clinical trials. Here, we analyzed this new physical treatment under non-ideal conditions such as may occur during patient treatment. Three established human PDAC cell lines BxPC-3, gemcitabine-resistant BxPC-3 (BxGem), AsPC-1, and a non-malignant primary pancreatic cell line CRL-4023 were treated with TTFields in vitro. MTT assays, electrical impedance measurement, cell staining with Annexin V/7AAD followed by FACS analysis, digital image analysis and immunohistochemistry were performed. Treatment with TTFields smaller than 0.7 V/cm and field lines in the direction of mitotic spindle orientation significantly inhibited proliferation of all PDAC cells at 150 kHz, but significantly increased viability of AsPC-1 cells at all frequencies between 100 kHz and 300 kHz and that of BxPC-3 and BxGem cells at 250 kHz. Apoptosis or necrosis were not induced. Non-malignant CRL-4023 cells were not affected at 150 kHz. TTFields damaged PDAC cell lines but even favored their viability at very weak field strength and unfavorable frequency or inadequate field direction.